Learning aid for use with. Basic marketing / E. Jerome McCarthy, William D. Perreault - Mccarthy, E. Jerome [et.al] (1993)
Marketing´s role in the global economy, marketing´s role within the fims or nonprofit organization, economics fundamentals, finding target market oppoortunities with markekt segmentation, evaluating opportunities in the changing marketing environment, getting informatin for marketing decisions, demographic dimensions of glboal consumer markets, place and development of channel systems, retailers and their strategy planning, wholesalers and their strategy, planning, pricing objectives and policies, controlling marketing plans and progrsams.